Late initiation of antiretroviral therapy: inequalities by educational level despite universal access to care and treatment - Amanda Rodrigues; Claudio J. Struchiner; Lara E. Coelho; Valdilea G. Veloso; Beatriz Grinsztejn; Paula M. Luz (BMC, 2021)
Abstract Background Late antiretroviral treatment initiation for HIV disease worsens health outcomes and contributes to ongoing transmission. We investigated whether socioeconomic inequalities exist in access to treatment in a setting with universal access to care and treatment. Methods This study investigated the association of educational level, used as a proxy for socioeconomic status, with late treatment initiation and treatment initiation with advanced disease. Study participants included adults (≥25 years) who started treatment from 2005 to 2018 at Instituto Nacional de Infectologia Evandro Chagas of Fundação Oswaldo Cruz (INI/FIOCRUZ), Rio de Janeiro, Brazil. Educational level was categorized following UNESCO's International Standard Classification of Education: incomplete basic education, basic education, secondary level, and tertiary level. We defined late treatment initiation as those initiating treatment with a CD4 < 350 cells/mL or an AIDS-defining event, and treatment initiation with advanced disease as those initiating treatment with a CD4 < 200 cells/mL or an AIDS-defining event. A directed acyclic graph (DAG) was constructed to represent the theoretical-operational model and to understand the involvement of covariates. Logistic regression models were used to estimate the adjusted odds ratios (aOR) and 95% confidence intervals (95%CI). Multiple imputation using a chained equations approach was used to treat missing values and non-linear terms for continuous variables were tested. Results In total, 3226 individuals composed the study population: 876 (27.4%) had incomplete basic education, 540 (16.9%) basic, 1251 (39.2%) secondary level, and 525 (16.4%) tertiary level. Late treatment initiation was observed for 2076 (64.4%) while treatment initiation with advanced disease was observed for 1423 (44.1%). Compared to tertiary level of education, incomplete basic, basic and secondary level increased the odds of late treatment initiation by 89% (aOR:1.89 95%CI:1.47-2.43), 61% (aOR:1.61 95%CI:1.23-2.10), and 35% (aOR:1.35 95%CI:1.09-1.67). Likewise, the odds of treatment initiation with advanced disease was 2.5-fold (aOR:2.53 95%CI:1.97-3.26), 2-fold (aOR:2.07 95%CI:1.59-2.71), 1.5-fold (aOR:1.51 95%CI:1.21-1.88) higher for those with incomplete basic, basic and secondary level education compared to tertiary level. Conclusion Despite universal access to HIV care and antiretroviral treatment, late treatment initiation and social inequalities persist. Lower educational level significantly increased the odds of both outcomes, reinforcing the existence of barriers to "universal" antiretroviral treatment.